An experimental study of thermal management system using copper mesh-enhanced composite phase change materials for power battery pack. (15th October 2016) - Wu, Weixiong; Yang, Xiaoqing; Zhang, Guoqing; Ke, Xiufang; Wang, Ziyuan; Situ, Wenfu; Li, Xinxi; Zhang, Jiangyun
Abstract: As an important method for battery thermal management, traditional phase change material (PCM) technology is facing challenges due to the relatively low thermal conductivity, weak skeleton strength and/or leakage phenomenon of PCM. Herein we develop a copper mesh (CM)-enhanced paraffin (PA)/expanded graphite (EG) composite as a composite PCM for battery thermal management. EG with porous structure can absorb liquid phase PA, preventing PA leakage. CM acts as a skeleton to further enhance both the thermal conductivity and strength of the whole module. As a result, the as-constructed CM enhanced PCM of PA/EG plate (PCMP) presents much better heat dissipation performance and temperature uniformity compared to PCMP without CM, especially in harsh working conditions. Moreover, with forced air convection, copper fins exposed from the composite may play a crucial role in not only heat dissipation, but also disturbing the air flow, and thus further strengthen the heat transfer capability. Highlights: Copper mesh-enhanced composite PCM (Cu-PCMP) is prepared and used in BTM system. Introducing copper mesh as a third component improves the cooling effect greatly. Combining forced air convention with Cu-PCMP further enhances the cooling effect. Exposed copper fin from the composite can strengthen heat transfer capability.